Transesterification of waste cooking oil: Quality assessment via thermogravimetric analysis. (February 2019) - Almazrouei, Manar; Elagroudy, Sherien; Janajreh, Isam
Abstract: Biodiesel is a good substitute for petrol-diesel at lower greenhouse emissions footprint. Biodiesel is commonly generated through transesterification of lipid, animal fat and waste cooking oil (WCO) with alcohol in the presence of catalyst. Assessment of the product quality of biodiesel and the byproduct for further utilization can be done using Thermogravimetric analysis (TGA) instead of more involved and specialized technique such as GC/MS and HLPC. TGA of biodiesel and the crude byproduct glycerol were investigated in this work following transesterification essay under different reactants ratio and catalysis concentrations. Biodiesel TA thermographs was characterized by four events and with two distinct peaks shown in the derivative of TGA curve. The crude glycerol showed three pronounced peaks. The best conversion of WCO to biodiesel was determined based on the fraction of biodiesel or the 2 nd TGA event. Highest conversion was obtained at 12:1 Methanol:WCO molar ratio 93% compared to 65%, 77% and 89% at 3:1, 6:1, 9:1 ratio, respectively. The influence of the catalyst is observed at lower molar ratio by advancing the conversion from 65% to 77% and 79% to 93% at 3:1 and 6:1 Methanol:WCO ratio, respectively. Higher glycerol quality was obtained at lower catalyst concentration.